The relationship between the leadership, internal quality, and customer satisfaction levels of dealerships in a South African motor vehicle organisation - Botha, Jennifer (Rhodes University, Faculty of Commerce, Department of Management, 2002)
This research investigates the relationship between the leadership, internal quality, and customer satisfaction levels in the dealerships of a South African motor vehicle organisation. The Service Profit Chain provides the background theory to this relationship, by suggesting that various factors within the service delivery system of an organisation affect the level of customer satisfaction. From the Service Profit Chain, it is established that two of the prevalent factors affecting customer satisfaction, are leadership and internal quality. The Full Range Leadership Development Theory provides the backdrop for analysing the leadership style of each dealership by using the Multifactor Leadership Questionnaire. The Competence Process forms the theoretical construct against which the internal quality of these dealerships is assessed using the Organisation Competence Analysis Questionnaire. Information was gathered, using these two instruments, from a sample of 85 motor vehicle dealerships within South Africa. The customer satisfaction levels at each of these dealerships, is measured by the motor vehicle organisation's own instrument, known as the Customer Satisfaction Index. Data obtained from each instrument, for the respective dealerships, was then statistically analysed. However, due to the low reliability of the instruments used in this research, the results of this study indicate that there is no relationship between the leadership, internal quality, and customer satisfaction levels within a South African motor vehicle organisation. Therefore we can conclude that the null hypotheses can not be rejected.
Keywords: Consumer satisfaction; Automobile dealers -- South Africa; Industrial productivity; Customer services